2018
DOI: 10.1080/21691401.2018.1455055
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylaminogalactosyl-decorated biodegradable PLGA-TPGS copolymer nanoparticles containing emodin for the active targeting therapy of liver cancer

Abstract: Primary liver cancer (PLC) is one of the most common malignant tumours and has the third highest mortality rate worldwide. An active liver-targeting drug delivery system via the asialoglycoprotein receptors expressed in the hepatic parenchyma cells of mammals has become a research focus for the treatment of PLC. N-acetylaminogalactosyl-poly(lactide-co-glycolide)-succinyl-D-α-tocopherol polyethylene glycol 1000 succinate (GalNAc-PLGA-sTPGS) was synthesized to achieve active liver-targeting properties. Emodin (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Finding more appropriate drugs or delivery methods with lower cytotoxicity and fewer side effects are important tasks for HCC chemotherapy. 14,15 Alkaloids are organic compounds containing nitrogen that occur nature, most of which are basic, some of which are neutral (eg, colchicine) or even acidic (eg, theophylline, theobromine). A wide range of pharmacological properties and effects have been reported, such as antimalarial (eg, quinine), antiasthma (eg, ephedrine), anticancer (eg, homoharringtonine), cholinomimetic (eg, galantamine), vasodilatory (eg, vincristine), antiarrhythmic (eg, quinidine), analgesic (eg, morphine), antibacterial (eg, chelerythrine), and antihyperglycemic activities (eg, vincristine and vinblastine).…”
Section: Discussionmentioning
confidence: 99%
“…Finding more appropriate drugs or delivery methods with lower cytotoxicity and fewer side effects are important tasks for HCC chemotherapy. 14,15 Alkaloids are organic compounds containing nitrogen that occur nature, most of which are basic, some of which are neutral (eg, colchicine) or even acidic (eg, theophylline, theobromine). A wide range of pharmacological properties and effects have been reported, such as antimalarial (eg, quinine), antiasthma (eg, ephedrine), anticancer (eg, homoharringtonine), cholinomimetic (eg, galantamine), vasodilatory (eg, vincristine), antiarrhythmic (eg, quinidine), analgesic (eg, morphine), antibacterial (eg, chelerythrine), and antihyperglycemic activities (eg, vincristine and vinblastine).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, various strategies such as surface modification, newly synthesized and porous have been developed to improve the PLGA nanoparticles. 30,47,48 In recent years, many studies have found that TPGS has many unique characteristics, such as absorption enhancer, mucosal immune adjuvant, and multi-drug resistance reversal property. TPGS can also be used as precursor drugs, micelles, and liposomes to improve the solubility, permeability, and stability of the preparation; thus, achieving sustained, controlled release and targeting effects.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles were synthesized without any problem and liver targeting was achieved smoothly. Nanoparticles increased the antitumoral effect of emodin both in vivo and in vitro, performing it a possible choice for the treatment of primary liver cancer [ 120 ]. Emodin has been observed to stimulate mitochondrial dysfunction and apoptosis in HepG2 cells by upregulation of cyclophilin D. Expression of Cyclophilin D was effectively inhibited by the epidermal growth factor and N-acetyl-L-cysteine.…”
Section: Anticancer Activity Of Emodinmentioning
confidence: 99%
“…As a result, GalNAc-PLGA-TGPS nanoparticles exhibited a stronger antiproliferative effect on the HepG2 cell compared to the free emodin. Better active targeting and higher levels of inhibition of liver cancer cells were observed in mice [ 120 ]. It can be said that the newly synthesized GalNAc-PLGA-TPGS biomaterial has an important role in active targeting with the increase in asialoglycoprotein receptor expression.…”
Section: Nano-drug Delivery Strategies For Emodinmentioning
confidence: 99%